1990
DOI: 10.1128/jcm.28.5.1009-1015.1990
|View full text |Cite
|
Sign up to set email alerts
|

Microbiology and potential virulence of Sporothrix cyanescens, a fungus rarely isolated from blood and skin

Abstract: Sporothrix cyanescens has been recovered from blood and a finger lesion at several medical centers in the United States. The morphology and physiology of these and three additional isolates were studied. S. cyanescens was distinguished from S. schencku and S. fungorum by white to lavender colonial pigmentation and from S. schenckii also by the formation of secondary conidia. Ail isolates of S. cyanescens grew well at 37°C, were cycloheximide susceptible, strongly urease positive, and benomyl resistant, failed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
37
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 16 publications
3
37
1
Order By: Relevance
“…Howard and Orr reported a thiamine requirement for the growth of S. schenckii [18]. In a more extensive study, Sigler et al showed that yeast forms of S. schenckii hydrolysed urea after 96 h of incubation [19]. We found a similar result with all those isolates of S. schenckii.…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…Howard and Orr reported a thiamine requirement for the growth of S. schenckii [18]. In a more extensive study, Sigler et al showed that yeast forms of S. schenckii hydrolysed urea after 96 h of incubation [19]. We found a similar result with all those isolates of S. schenckii.…”
Section: Discussionsupporting
confidence: 82%
“…Conidiation was better observed on CMA as compared to SDA and PDA. Earlier studies with environmental or clinical isolates found no significant difference in the colony characters [18][19][20]as all the isolates grew well between the temperatures of 30 and 37°C but failed to grow at a temperature of 40°C. In an earlier study it was reported that environmental isolates grew better at 30°C and even at 35°C, however, the clinical isolates grew at 37°C [18,19].…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations